Prevalence of ABO and rhesus blood groups in blood donors: a study from a tertiary care centre in south Gujarat, India - Mistry, Sunita; Patel, Kamini; Shah, Kamlesh (Tropical Journal of Pathology and Microbiology, 2019)
Background: Since it was discovered by Karl Landsteiner, the ABO blood group system is the most important blood group system in Transfusion Medicine. ABO and Rhesus (Rh) blood group antigens are hereditary characters and are useful in population genetic studies, in resolving medico-legal issues and more importantly for the immunologic safety of blood during transfusion. Aims: This study was carried out to determine the frequency and distribution of ABO and Rhesus (Rh) blood groups in blood donors of tertiary care hospital-attached blood bank and compare it with other data from similar studies within the India. Materials and Methods: This study was conducted among the blood donors of GMERS Medical College and Hospital, Valsad Gujarat State (India), who donated blood during the period from January 2017 to December 2018. ABO and Rh blood grouping was performed by forward blood grouping (cell grouping) using test tube agglutination method using antisera A, antisera B and antisera D and by reverse grouping (serum grouping) using pooled known A, B and O cells. Results: Out of 2971 blood donors, 2746 (92.42%) were male and 225(7.57%) were female. The blood group frequencies positions in the descending order were ‘O’, ‘B’, ‘A’ and ‘AB’ respectively. Rh positive donors were 97.54% and Rh negative were 2.45%. One group was ‘Oh’ (Bombay Phenotype). Conclusions: ‘O’ group is the most frequent position of ABO blood group system followed by ‘B’ group. Rh+ is the most frequent group than Rh- in the Rh system. Blood donations by females are very low.